The association between the gut microbiome and 24-h blood pressure measurements in the SCAPIS study - Yi-Ting Lin; Sergi Sayols-Baixeras; Gabriel Baldanzi; Koen F. Dekkers; Ulf Hammar; Diem Nguyen; Nynne Nielsen; Aron C. Eklund; Georgios Varotsis; Jacob B. Holm; H. Bjørn Nielsen; Lars Lind; et al. (Communications Medicine)
Abstract Background There is mounting evidence supporting the role of the microbiota in hypertension from experimental studies and population-based studies. We aimed to investigate the relationship between specific characteristics of the gut microbiome and 24-h ambulatory blood pressure measurements. Methods The association of gut microbial species and microbial functions, determined by shotgun metagenomic sequencing of fecal samples, with 24-h ambulatory blood pressure measurements in 3695 participants and office blood pressure was assessed in multivariable-adjusted models in 2770 participants without antihypertensive medication from the Swedish CArdioPulmonary bioImage Study. Results Gut microbiome alpha diversity was negatively associated with diastolic blood pressure variability. Additionally, four microbial species were associated with at least one of the 24-h blood pressure traits. Streptococcus sp001556435 was associated with higher systolic blood pressure, Intestinimonas massiliensis and Dysosmobacter sp001916835 with lower systolic blood pressure, Dysosmobacter sp001916835 with lower diastolic blood pressure, and ER4 sp900317525 with lower systolic blood pressure variability. Moreover, office blood pressure data from a subsample without ambulatory blood pressure measurements replicated the association of Intestinimonas massiliensis with systolic blood pressure and Dysosmobacter sp001916835 with diastolic blood pressure. Species associated with 24-h blood pressure were linked to a similar pattern of metabolites. Conclusions In this large cross-sectional analysis, gut microbiome alpha diversity negatively associates with diastolic blood pressure variability, and four gut microbial species associate with 24-h blood pressure traits.